Enterprise Resource Planning (ERP) Evaluation using User Experience Questionnaire and Development of Chatbot for Indonesian Insurance Company - Ryang Agung; Jansen Wiratama; Suryasari (Universitas Islam Raden Rahmat, Malang, 2023)
Implementing Enterprise Resource Planning (ERP) can facilitate the planning and management of company resources. One of the insurance companies in Indonesia implementing ERP is PT Asuransi Jiwa Manulife; the platform used is a cloud-based ERP from Infor company, namely Infor CloudSuite. The Cloud ERP feature used is MiPOS, a part of making insurance proposals for prospective customers. In the implementation of MiPOS, there are still deficiencies in User Experience (UX) which are not yet user-friendly; therefore, a UX evaluation on MiPOS is carried out using the User Experience Questionnaire (UEQ) method distributed to MiPOS users as respondents. UEQ is a complete User Experience assessment framework that captures a person's impression of a system. UEQ has six aspects with 26 assessment criteria as a measure. However, in this research, the measurement was focused on the Perspicuity aspect. The research results show that the Perspicuity aspect score has the lowest value, namely -0.379 points, which falls into the neutral category. The effects of the Perspicuity aspect form the basis for ERP development by creating Frequently Asked Questions (FAQ) pages equipped with the Chatbot feature.